2005
DOI: 10.1095/biolreprod.104.035048
|View full text |Cite
|
Sign up to set email alerts
|

Affinity-Dependent Alterations of Mouse B Cell Development by Noninherited Maternal Antigen1

Abstract: We have examined the passage of maternal cells into the fetus during the gestation and postpartum in mice. Using enhanced green fluorescent protein (EGFP)-transgenic females, we showed that maternal cells frequently gain access to the fetus, mostly in syngeneic pregnancies, but also in allogeneic and outbred crosses. EGFP-transgenic cells, including B, T, and natural killer cells, can persist until adulthood, primarily in bone marrow and thymus. We then asked whether maternal cells, bearing antigens not inheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 58 publications
2
30
0
Order By: Relevance
“…Mothers expressing H-2 k or H-2 b Ags did not tolerize offspring that failed to inherit these Ags (J. Andrassy and M. L. Molitor-Dart, submitted for publication). Similarly, interstrain differences in NIMA effect were noted by Vernochet et al (54) who found that maternal cells influence the development of fetal and neonatal allospecific B cells, and that affinity played a large role in the outcome of this maternal influence.…”
Section: Discussionsupporting
confidence: 53%
“…Mothers expressing H-2 k or H-2 b Ags did not tolerize offspring that failed to inherit these Ags (J. Andrassy and M. L. Molitor-Dart, submitted for publication). Similarly, interstrain differences in NIMA effect were noted by Vernochet et al (54) who found that maternal cells influence the development of fetal and neonatal allospecific B cells, and that affinity played a large role in the outcome of this maternal influence.…”
Section: Discussionsupporting
confidence: 53%
“…Maternal microchimerism has been shown in mice to induce neonatal B cell (26) and probably also T cell (27) tolerance and is therefore one of the possible mechanisms for NIMA effects (28). Although speculative, we postulate therefore that the protective effect of the DERAA-containing HLA-DRB1 alleles as NIMA on the development of RA is most probably mediated by maternal cells entering the bloodstream and tissues of the child, which exert their effect through a change in the immune repertoire and, most likely, the T cell repertoire of the child.…”
Section: Discussionmentioning
confidence: 99%
“…However, this needs to be investigated in different strain combinations because in a recent study using a transgenic mouse model, exposure to NIMAs was shown to either down-regulate or upregulate the allogeneic B-cell responses depending on the NIMA haplotypes. 18 In contrast to the NIMA effects, it remains controversial whether the maternal exposure to IPAs induces tolerance in clinical transplantation. 19 Survival rates after BMT from a maternal donor were better than those after BMT from a paternal donor.…”
Section: Discussionmentioning
confidence: 99%